Extended high-frequency audiometry in healthy adults with different age groups - Mingming Wang; Yu Ai; Yuechen Han; Zhaomin Fan; Peng Shi; Haibo Wang (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background It was well-documented that extended high-frequency (EHF, above 8 kHz) hearing test could be more sensitive comparing with the conventional measurement on frequency below 8 kHz, regarding the early prediction of auditory damage in certain population. However, hardly any age-specific thresholds of EHF in population with normal hearing ability were observed. This study aims to monitor the age-dependent hearing thresholds at EHF (from 9 to 20 kHz) in healthy hearing population. Methods A total of 162 healthy participants (from 21 to 70 years) with normal conventional pure tone audiograms were recruited and separated into five groups by age. Conventional pure tone average was performed with frequencies from 0.25 to 8 kHz under air conduction and from 0.25 to 4 kHz under bone conduction. EHF audiometry from 9 to 20 kHz was determined under air conduction. Results The effects of aging on hearing were evident at frequencies above 4 kHz. The hearing thresholds of EHF were less than 26 dB HL before 30 years-olds. Hearing abilities in EHF were deteriorated starting from the 31 ~ 40 group and were most obvious in the 51 ~ 60 group and the 61 ~ 70 group with the maximum thresholds of 75 dB HL. Sensitivity of EHF was inversely proportional to the frequency within each age group, and to age among groups. Subjects under 30 years old were totally responsive up to 16 kHz, and 52.2% could respond to 20 kHz. Meanwhile, no responsiveness was recorded to 20 kHz in the 51 ~ 60 group and even to 18 kHz in the 61 ~ 70 group. No gender differences in hearing threshold was observed within each age group, except an obvious decline at frequencies of 4, 6, 8, and 9 kHz in male participants of the 41 ~ 50 group. Conclusions Hearing thresholds at EHF from 9 to 20 kHz were more sensitive than at frequencies below 8 kHz for hearing measurement, and aging inversely affected hearing ability at EHF in healthy population. Hearing thresholds at EHF deteriorated with age and raising frequency, while the upper frequency limit decreased with aging. Graphical abstract